Inflammatory Status is Different in Relationship to Insulin Resistance in Severely Obese People and Changes after Bariatric Surgery or Diet-induced Weight Loss - Ballesteros-Pomar, M. D.; Calleja, S.; Díez-Rodríguez, R.; Calleja-Fernández, A.; Vidal-Casariego, A.; Nuñez-Alonso, A.; Cano-Rodríguez, I.; Olcoz-Goñi, J. L. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Aim: To assess if insulin resistance is related to a different inflammatory status (especially lymphocyte subpopulations) in severely obese people and to evaluate changes after weight loss either following a very-low calorie diet (VLCD) or bariatric surgery.Research Methods & Procedures: Severely obese patients were consecutively recruited in our Obesity Unit. Blood lymphocyte subpopulations and inflammatory parameters were measured baseline, after a VLCD during 6 weeks and one year after biliopancreatic diversion. Insulin resistance was evaluated by Homeostasis Model Assessment (HOMA) index.Results: After excluding diabetic patients, 58 patients were studied. HOMA index classified 63.8% of them as insulin resistant (IR). Serum baseline levels of inflammatory cytokines were not significantly different between IR and insulinsensitive (IS) patients but, regarding lymphocyte subpopulations, Natural Killer (NK) cells were higher in IR patients [(305.0 (136.7) vs. 235.0 (80.7) cells/µL, p=0.047]. NK cells showed a significant positive correlation with HOMA index (r=0.484, p=0.000) and with the carbohydrate content of the diet (r=0.420, p=0.001). After VLCD, NK cells significantly decreased, but only in IR patients and in those losing more than 10% of their initial weight. After biliopancreatic diversion, total and CD8 T Lymphocytes, B lymphocytes and NK cells also decreased but only in IR individuals.Conclusion: NK cells are significantly increased in IR severely obese people in respect to IS, suggesting a slightly different immune status in these patients with a probable dietary relationship. Weight loss could reverse this increase either after VLCD or after bariatric surgery.
Keywords: obesity; insulin resistance; lymphocytes; NK cells; bariatric surgery; very low calorie diet